Proceedings of the seminar-workshop on aquaculture development in Southeast Asia and prospects for seafarming and searanching : (Aquaculture Department Southeast Asian Fisheries Development Center, 1994)
This volume of ADSEA '91 contains review papers on aquaculture research and development as well as regional and country experiences.